2022
DOI: 10.1007/jhep08(2022)133
|View full text |Cite
|
Sign up to set email alerts
|

Interior structure and complexity growth rate of holographic superconductor from M-theory

Abstract: We study the interior dynamics of a top-down holographic superconductor from M-theory. The condense of the charged scalar hair necessarily removes the inner Cauchy horizon and the spacetime ends at a spacelike singularity. Although there is a smooth superconducting phase transition at the critical temperature, the onset of superconductivity is accompanied by intricate interior dynamics, including the collapse of the Einstein-Rosen bridge, the Josephson oscillations of the condensate, and the final Kasner singu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Indeed, we see fluctuations in the a-function which leave an imprint on the derivative. This and the other fluctuations in the interior functions (Appendix B.2) are reminiscent of the Josephson oscillations in the holographic superconductor [30,31]. Furthermore, such oscillations in the derivative allow it to reach 0 (numerically).…”
Section: 15)mentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, we see fluctuations in the a-function which leave an imprint on the derivative. This and the other fluctuations in the interior functions (Appendix B.2) are reminiscent of the Josephson oscillations in the holographic superconductor [30,31]. Furthermore, such oscillations in the derivative allow it to reach 0 (numerically).…”
Section: 15)mentioning
confidence: 98%
“…Phase transitions It would be interesting to conduct a more thorough analysis of holographic p-wave superfluid states [24,54] so as to see how the a-function may be sensitive to the phase structure of the underlying theory. One may also consider the a-function in other setups exhibiting phase transitions, such as the holographic superconductor [30,31] or round black holes [55].…”
Section: Other Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further phenomenon that appears in these works are bounces between different Kasner 'epochs', see e.g. [14,16,21,25,[27][28][29]. This is again familiar from much earlier work, most famously the chaotic bounces of the 'mixmaster' universe [30].…”
mentioning
confidence: 92%
“…A recent body of work has demonstrated that a common feature of (minisuperspace) holographic interiors is the emergence of Kasner scaling towards the singularity [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
mentioning
confidence: 99%